Simple design of memristive counters and their applications in automatic irrigation system. Issue 1 (3rd January 2020) - Raj, P. Michael Preetam; Louis, V. Jeffry; Viswakumar, Aditya; Kundu, Souvik
Abstract : Memristor, a passive circuit element got tremendous research attention for its in‐memory computation. In this study, it was identified that controllable resistive state transitions exist within a single memristor. On the basis of this realisation, a simple but unconventional implementation of memristive up and down counters was presented. Furthermore, a dual up–down counter was developed, which can mimic any real‐time process variations. To demonstrate its practical application, a counter‐based memristive automatic irrigation system was explicated, which provided optimised utilisation of electrical and water resources. The proposed study opens up a new purview in the area of future non‐Von Neumann computer architectures and its potential electronic applications.